PEMBELAJARAN MENULIS TEKS BIOGRAFI PADA SISWA KELAS X SMA NEGERI 3 SEKADAU HILIR - Utami Tri Yanti; Ahmad Rabi’ul Muzammil; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis thesis is a common problem, namely "How does Learning write biographical texts to students of grade X SMA Negeri 3 Sekadau Hilir in the 2019/2020 school year?". The purpose of this study describes the problem, while this research is useful for researchers to increase knowledge and insight in analyzing biographical text learning, and can be used by teachers and students as a learning medium and as a comparison material for other research. This thesis uses descriptive method, qualitative research form. In addition, the results of data analysis can be concluded that the learning of writing biographical texts to grade X students of SMA Negeri 3 Sekadau Hilir is reviewed from category learning planning in accordance with the teacher's reasoning in accordance with the learning planning guidelines. Then the implementation of good category learning on the grounds that teachers are able to carry out learning in accordance with the guidelines of the implementation of teaching teachers. And the results of learning to write biographical texts by students are seen from aspects of categorized content (capable), from aspects of categorized structures (very capable), and from aspects of categorized language rules (enough). In addition, the results of this study can be implemented in Learning Bahasa Indonesia in high school, especially in grade X students of Odd semester. The authors hope this research can be continued by further researchers to research from others. For example, learning to write biography texts of Ir Soekarno to other grade X students of SMA Negeri.Keywords: learning, writing, biographical text